2011
DOI: 10.1016/j.ejcts.2011.01.062
|View full text |Cite
|
Sign up to set email alerts
|

Elephant trunk procedure 27 years after Borst: what remains and what is new?

Abstract: The treatment of complex aortic pathology involving both the ascending and descending aortic segments at the same time represents a surgical challenge, with high postoperative morbidity and mortality rates reported. Over the past 27 years, different open surgical and endovascular techniques have been introduced and applied in various two-stage- or one-stage approaches to such cases. Thus, in 1983, Hans Borst significantly changed the traditional two-stage approach by introducing his elephant trunk technique. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 105 publications
(246 reference statements)
5
52
1
3
Order By: Relevance
“…Those two characteristics mark the main difference with other branched prostheses. The 30-day mortality of 5 % (n = 1) we experienced in our relatively small cohort fits the mortality rates reported by other authors (3.7-18.4 %) [16][17][18].…”
Section: Commentsupporting
confidence: 89%
See 2 more Smart Citations
“…Those two characteristics mark the main difference with other branched prostheses. The 30-day mortality of 5 % (n = 1) we experienced in our relatively small cohort fits the mortality rates reported by other authors (3.7-18.4 %) [16][17][18].…”
Section: Commentsupporting
confidence: 89%
“…With a 33 % rate of 2nd-stage procedure after a mean follow-up of 9.6 months, Fig. 3 Kaplan-Meier survival curve we report numbers lower than the average of 45 % reported in a recent review by Lus and co-workers [18], but the same as the 32 % reported by Shresta et al [26]. We indicated the ET procedure for patients with type A dissection even if the diameter of the dissected descending aorta was normal, because a large number of patients might develop aneurysm of the descending aorta later on [27] and it carries no additional risk compared to the standard arch replacement [26].…”
Section: Commentcontrasting
confidence: 74%
See 1 more Smart Citation
“…18 A worldwide experience of FET and its variations was recently analyzed in a population of 700 patients including 400 of both acute and chronic dissections, the mean perioperative mortality in dissection patients was 6% with Ius et al 3 A perioperative mortality of 14.7% in our study using sFETT is at least comparable to these prior reports and can be considered low given the fact that we performed sFETT only in patients with compromised aortic branch vessels a known risk factor for malperfusion and in hospital mortality. 3,19,20 The impact of the sFETT on the evolution of postoperative aortic dissection is impressive. After sFETT, there was a significantly lower incidence of branchvessel compromise the supraaortic vessels (40.7% vs. 17.5%; p < 0.05) and the renovisceral arteries (29.6% vs. 17.2%; p < 0.05) ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Latter floating graft facilitates secondary descending aortic repair through a lateral thoracotomy. [2][3][4] A major drawback of the ET technique is that the distal arch anastomosis might be challenging or impossible to seal especially when it is performed in patients with a severe coagulation disorder, as commonly encountered in acute aortic dissections. To face these drawbacks, the frozen elephant trunk (FET) technique was developed and first described in 2003.…”
Section: Introductionmentioning
confidence: 99%